Boiling Frogs: Pricing Strategies for a Manufacturer Adding a Direct Channel that Competes with the Traditional Channel - Cattani, Kyle; Gilland, Wendell; Heese, Hans Sebastian; Swaminathan, Jayashankar (Production and Operations Management, 2006)
We analyze a scenario where a manufacturer with a traditional channel partner opens up a direct channel in competition with the traditional channel. We first consider that in order to mitigate channel conflict the manufacturer, who chooses wholesale prices as a Stackelberg leader, commits to setting a direct channel retail price that matches the retailer's price in the traditional channel. We find that the specific equal‐pricing strategy that optimizes profits for the manufacturer is also preferred by the retailer and customers over other equal‐pricing strategies. We next consider the implications of the equal‐pricing constraint through a numerical experiment that indicates that the equal‐pricing strategy is appropriate as long as the Internet channel is significantly less convenient than the traditional channel. If the Internet channel is of comparable convenience to the traditional channel, then the manufacturer has tremendous incentive to abandon the equal‐pricing policy, at great peril to the traditional retailer.